THE RELATIONSHIP WITH EMPLOYEE PLACEMENT AND TRAINING WITH EMPLOYEE ACHIEVEMENT AT PT. BANK BENGKULU - Wahyu Hidayat; Ahmad Soleh; Kaulan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
Placement of employees in the right position will help the company to get optimal work results and achieve the expected goals. Apart from the placement of employees, another thing that must be considered by the company in improving job performance is job training for employees. The purpose of this study is to determine the correlation between placement and job training with employees performance at PT. Bank Bengkulu. The sample in this study were 87 permanent employees at PT. Bank Bengkulu Central Office, due to all the population in this study were sampled, the census sampling method was used. Data collection methods used were questionnaires and analytical methods with Spearman rank correlation and hypothesis testing. The results showed that Placement has a moderate correlation with employees performance at PT. Bank Bengkulu with a correlation value of 0.491, means that the more precise the placement, the better the work performance of employees at PT. Bank Bengkulu. This result is strengthened by the results of the hypothesis test that tcount is greater than t table (5.196> 1,662). Thus, the hypothesis test results are rejected H01 and Ha1 accepted, meaning that the placement has a significant correlation with employees work performance at PT. Bank Bengkulu. Job training has a strong correlation with employees performance at PT. Bank Bengkulu, with a correlation value of 0.747, means that increasing job training will increase employees performance at PT. Bank Bengkulu. This is reinforced by the results of hypothesis testing known that t count is greater than t table (10.359> 1.662). Thus, the hypothesis test results are H02 rejected and Ha2 accepted, meaning that job training has a significant correlation with employees work performance at PT. Bank Bengkulu.